2021
DOI: 10.1111/adb.13115
|View full text |Cite
|
Sign up to set email alerts
|

FGF2 is an endogenous regulator of alcohol reward and consumption

Abstract: Alcohol use disorder (AUD) is a chronic, relapsing disorder, characterized by escalating alcohol drinking and loss of control, with very limited available treatments. We recently reported that the expression of fibroblast growth factor 2 (Fgf2) is increased in the striatum of rodents following long-term excessive alcohol drinking and that the systemic or intra-striatal administration of recombinant FGF2 increases alcohol consumption. Here, we set out to determine whether the endogenous FGF2 plays a role in alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
2
5
0
Order By: Relevance
“…We observed that male C57BL/6J mice that were offered intermittent access to 20% ethanol and water voluntarily consumed stable amounts of ethanol with an average of 9g/kg/24 h ( Supplemental Figure S1a ). These results are consistent with other studies showing that male C57BL/6J mice consumed similar levels (10 g/kg/24 h) when offered 20% of alcohol [ 33 ]. Furthermore, mice lacking FGF-2 consumed significantly lower amounts of ethanol compared with wild-type mice [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We observed that male C57BL/6J mice that were offered intermittent access to 20% ethanol and water voluntarily consumed stable amounts of ethanol with an average of 9g/kg/24 h ( Supplemental Figure S1a ). These results are consistent with other studies showing that male C57BL/6J mice consumed similar levels (10 g/kg/24 h) when offered 20% of alcohol [ 33 ]. Furthermore, mice lacking FGF-2 consumed significantly lower amounts of ethanol compared with wild-type mice [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with other studies showing that male C57BL/6J mice consumed similar levels (10 g/kg/24 h) when offered 20% of alcohol [ 33 ]. Furthermore, mice lacking FGF-2 consumed significantly lower amounts of ethanol compared with wild-type mice [ 33 ]. Altogether, this leads to the assumption that multiple cycles of heavy drinking bouts and withdrawal periods lead to neuroadaptations in certain brain areas that induce ethanol dependence and addiction [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Systemic administration of recombinant FGF-2 (rFGF-2) increased alcohol consumption in mice, whereas inhibition of endogenous FGF-2 reduced alcohol intake (Even-Chen et al, 2017). Recently, it was also shown that mice lacking endogenous FGF-2 consumed lower amounts of alcohol, an alcohol-specific effect, as the intake and preference of sucrose, a natural reward, was unaffected (Even-Chen et al, 2022). These results support our present finding that FGF-2 KO mice consume less alcohol compared with wild types, manifesting FGF-2 as an important regulator of alcohol drinking behaviour in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity to EtOH reflects the threshold to become sedated in response to the inhibition of CNS activity (Chen et al, 2021; Childs et al, 2019; Ozburn et al, 2013). Individual sensitivity to EtOH is determined by the interaction between the pharmacological effect of EtOH and individual responses to EtOH (Even‐Chen et al, 2017, 2022; Ye et al, 2021). Our study was designed to clarify the mechanism underlying sensitivity to the sedative‐hypnotic effect of EtOH in mice.…”
Section: Discussionmentioning
confidence: 99%